Relationship between features of thinking and the ability to knowledge transfer of students - Lysak, K.A.; Lutsenko, O.L.; Луценко, О.Л. (My University, 2013)
The problems about student’s ability to apply theoretical knowledge in real and non training situations are discussed in the article. The definition of knowledge and knowledge transfer are given, distinctive features of the declarative and procedural knowledge are described. Attention is paid to the efficiency of transfer declarative knowledge to the procedural level. Results of the investigation of relationship between the ability to knowledge transfer and cognitive characteristics of students are presented. The significant connections between ability to knowledge transfer and critical thinking level, level of logical thought and anticipation are shown. The conclusions about future direction of research are made.
Keywords: declarative and procedural knowledge; knowledge transfer; critical thinking; logical thought; reflexivity; anticipation